Correction: Laboratory demonstration of the vertical transmission of Rift Valley fever virus by Culex tarsalis mosquitoes. - Nicholas A Bergren; Erin M Borland; Daniel A Hartman; Rebekah C Kading (Public Library of Science (PLoS), 2022)
[This corrects the article DOI: 10.1371/journal.pntd.0009273.].